2021
DOI: 10.3390/jcm10173996
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Systemic Lupus Erythematosus: An Update on Its Impact, Determinants and Therapeutic Management

Abstract: Fatigue is a complex and multifactorial phenomenon which is often neglected by clinicians. The aim of this review was to analyze the impact, determinants and management of fatigue in patients with Systemic Lupus Erythematosus (SLE). Fatigue is one of the most prevalent symptoms in SLE, reported by 67% to 90% of patients. It is also described as the most bothersome symptom, considering that it may impair key aspects of health-related quality of life, while also leading to employment disability. It is a multifac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…This result further supports the fact that fatigue in SLE is influenced by combinations of several factors rather than a single factor. 3,6 In this study, psychosocial stressors, such as histories of major personal illness and changes in eating habits, were significantly associated with fatigue in LLDAS patients. Therefore, although the patient is already in low disease activity, identification of major personal illness and change in eating habits is still recommended in terms of identification of risk factors and prevention of fatigue in SLE patients.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This result further supports the fact that fatigue in SLE is influenced by combinations of several factors rather than a single factor. 3,6 In this study, psychosocial stressors, such as histories of major personal illness and changes in eating habits, were significantly associated with fatigue in LLDAS patients. Therefore, although the patient is already in low disease activity, identification of major personal illness and change in eating habits is still recommended in terms of identification of risk factors and prevention of fatigue in SLE patients.…”
Section: Discussionmentioning
confidence: 60%
“…This is consistent with the study of Kawka et al which stated that even though disease activity has a complex contribution to fatigue, psychosocial factors seemed to provide the most important contribution. 3 Based on the MINI examination, most of the participants had a generalized anxiety disorder (30.1%), depression (16.4%), and dysthymia (12.3%). These were in line with several studies which found mood disorders such as depression and anxiety disorders to be very common in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatigue is a general and continued feeling of tiredness or difficulty performing physical and mental activities for days to weeks, which is not resolved by rest (5) . Fatigue is the most common and disabling symptom in SLE that may impair female patients' physical and mental health and reduce quality of life by impacting upon their emotions, work, and daily life activities (6) . Non-pharmacological interventions and lifestyle arrangements are very important in disease management, these include female education, protection from sunlight, rest and the reduction of fatigue, use of medication, infection control, vaccination, a diet low in salt, fat and cholesterol, avoidance of stress, pregnancy and contraception and reduction of psychosocial effects (7) .…”
Section: Introductionmentioning
confidence: 99%